2018
DOI: 10.1302/0301-620x.100b2.bjj-2017-1016.r1
|View full text |Cite
|
Sign up to set email alerts
|

Three groups of dissatisfied patients exist after total knee arthroplasty: early, persistent, and late

Abstract: Three groups of dissatisfied patients exist after TKA: 'early' dissatisfaction at one year, 'persistent' dissatisfaction with longer follow-up, and 'late' dissatisfaction developing in previously satisfied patients at one year. All three groups have different independent predictors of satisfaction, and potentially addressing risk factors specific to these groups may improve patient outcome and their satisfaction. Cite this article: 2018;100-B:161-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 23 publications
2
55
1
1
Order By: Relevance
“…and that walking aids may still be required up to 10 years following surgery. Clement et al [24] described 3 groups of dissatisfied patients that exist after TKAdearly (1 year), persistent (continued dissatisfaction with long-term follow-up), and late (new dissatisfaction in previously satisfied patients). It was identified that independent predictors of dissatisfaction at 1 year differed to those which predicted dissatisfaction at 5 years, suggesting that these groups have different characteristics.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Pmentioning
confidence: 99%
“…and that walking aids may still be required up to 10 years following surgery. Clement et al [24] described 3 groups of dissatisfied patients that exist after TKAdearly (1 year), persistent (continued dissatisfaction with long-term follow-up), and late (new dissatisfaction in previously satisfied patients). It was identified that independent predictors of dissatisfaction at 1 year differed to those which predicted dissatisfaction at 5 years, suggesting that these groups have different characteristics.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Pmentioning
confidence: 99%
“…Thus, Katchky indicate that despite generally good outcomes after TKA, between 15% and 20% of patients remain dissatisfied [31]. This number decreases over time as patients adapt to their knee systems [47] ( Table III). The advantage of the Knee Society Scoring System is that neither age nor the general health condition of the patient affects the scoring, but such factors as age, body mass index, rehabilitation compliance, and the presence of other diseases like diabetes may be a factor.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are similar to those seen in the hip and knee arthroplasty literature. 4,6,7,14,20,21,27 The rate of comorbid back pain is lower in patients who had shoulder instability than in patients undergoing hip and knee arthroplasty. Our patients had a 15.8% incidence of comorbid back pain, whereas Parvizi et al 20 reported a 49.4% rate in a review of 344 patients undergoing total hip arthroplasty, and Clement et al 7 found an incidence of 35% in a subset of 2392 patients undergoing primary total knee arthroplasty (TKA).…”
Section: Discussionmentioning
confidence: 99%
“…Depression is also a known independent risk factor for dissatisfaction after TKA. 6 Future studies are needed to further evaluate the relationship between worse mental health scores, depression, and postoperative outcomes in shoulder instability.…”
Section: Discussionmentioning
confidence: 99%